CONSTRUCTION AND VALIDITY OF USABILITY OF APPLICATION PROTOTYPE FOR KNOWLEDGE DISSEMINATION OF TEXTO & CONTEXTO ENFERMAGEM JOURNAL. - Boneli da Silva, Marinalda; Capellari Fabrizzio, Greici; Ribeiro de Jesus, Edna; Couto Carvalho Barra, Daniela; Lorenzini, Elisiane (Texto & Contexto Enfermagem, 2024)
Objective: To construct and validate a prototype mobile application for disseminating scientific knowledge from Texto & Contexto Enfermagem journal. Method: A methodological study of technological production that followed the stages of Design Thinking: empathize, define, ideate, prototype and test. The prototype was developed using the Figma© platform and was subsequently validated by a committee of judges who analyzed the prototype content using the Educational Content Validity Instrument in Health adapted for this study. In the pre-test, the System Usability Scale questionnaire was applied to students and professors of a Graduate Program in Nursing. The analysis was performed using the Content Validity Index and Kappa coefficient, where cut-off values of 0.80 and 0.60 were considered, respectively. Results: The prototype was developed through technological prospecting and interviews with the target audience. Afterwards, the prototype was validated by a committee composed of seven judges. To validate the prototype, two rounds of assessments were carried out by a committee of judges, in which the mean content validity index was 85.5 and Kappa of 0.729, resulting in the final version of the prototype. Subsequently, the pre-test phase was carried out. Thirty-four graduate nursing students participated in this phase, resulting in 85.3% usability by the target audience. Conclusion: The prototype developed and assessed in this study proved to be an innovative tool in disseminating scientific knowledge in nursing, allowing quick and practical access to scientific productions, presenting a tool with the potential to reach the academic public in health and nursing.